Kiều hối và “Căn bệnh Hà Lan” ở các nước đang phát triển Châu Mỹ La Tinh - Nguyen Phuc , Hien; Duong Bich, Dung (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
Recently, the amount of remittances as a source of capital flows to developing countries, including Latin America, has increased dramatically. The aim of the paper, therefore, is to investigate whether the symptom of the Dutch disease in Latin America or not. By applying System Generalized Methods of Moment (S-GMM) for the linear dynamic panel data (DPD) model from 20 countries during the period from 2006 to 2018, this paper examines the impact of remittances on the real effective exchange rate (REER). Our finding indicates that as remittances per capita increase by 1%, the real effective exchange rate of these countries appreciates by 0.0316%. Thus, this paper indicates that American Latin countries with a huge amount of remittance (higher 10% of GDP) have been faced strongly by the symptom of the Dutch disease. In addition, the selected countries with high export ratios (at the group of q75) and also have had the same effect. The authors also consider types of exchange regimes, the floating regime countries result in appreciation of real exchange rate supporting the existence of Dutch disease.